Peran Mediasi Komitmen Afektif Dan Kontrak Psikologis Pada Hubungan Antara Dukungan Organisasi Dan Berbagi Pengetahuan - Ardiawan, Alvin (Jurnal Ilmu Manajemen, 2021)
This study aims to determine the mediating role of affective commitment and psychological contract on the relationship between organizational support and knowledge sharing to employees of CV. BHAKTI ASTAWIRA SEJAHTERA. The object of this research is the employee of CV. BHAKTI ASTAWIRA SEJAHTERA. The research was conducted by distributing questionnaires to a research sample of 50 employees. The method in this study uses quantitative analysis methods. The sampling technique used non-probability sampling with saturated samples, that is, all members of the population were taken as samples. The analytical tools used are the validity test, reliability test, classical assumption test, T-test, F test, and Sobel test. Using SPSS 16 found the following results, firstly organizational support has a positive and significant effect on psychological contracts, secondly, organizational support has a positive and significant effect on affective commitment, thirdly organizational support has a positive and significant effect on knowledge sharing, the four psychological contracts have a positive and significant effect on knowledge sharing, the five affective commitments have no positive and insignificant effect on knowledge sharing.